Close Loop Control of Daylight - Artificial Light Integrated System - Padiyar U., Suprabha; Kamath, Vedavyasa; Ramachandra, Shruthi (International Journal of Engineering and Technology, 2018)
The paper proposes a system to achieve optimal lighting level in a given workspace where the user can define the amount of lux level required on the workplane. A hardware-software interface model is developed with close loop control mechanism to maintain the user-defined lux level, this is achieved by continuous monitoring of the light level and dynamic control of window blinds and dimming of artificial light system. Since illuminance level in the space is influenced by daylight and artificial light, a lighting fixture with CFL connected to 1-10V dimmable HF electronic ballast and window blinds controlled by servo motor are incorporated in the workspace. Based on the feedback obtained by the LDR sensor module placed on the floor of the workspace, PID control algorithm programmed in LabVIEW actuates the servo motor and the ballast. NI-LabVIEW along with NI-USB6008DAQ card is used to monitor and control lighting. Â